ECONOMICS OF WILD TURKEY MANAGEMENT - James C. Kroll; James R. Attebury; Michael H. Legg (Wildlife Society Bulletin)
Abstract Questionnaires were mailed to the 50 state wildlife agencies and 177 private turkey shooting preserves. Forty‐seven agencies and 58 private preserves responded. State responses indicated a general lack of information on expenditures for turkey management. Only three states had viable hatchery programs. Turkey stocking programs were responsible for releasing over 7,000 birds in 1974, the vast majority (6,000) in Pennsylvania. At shooting preserves, capital investments and annual maintenance costs far exceeded annual incomes. Sixty‐two percent of the responding preserves were operated as a secondary source of income, and probably serve as long term investments, tax deductions and/or hobbies.